Accounting Education, Lockdown, and Digital Media: Challenges, Opportunities, Tensions, and Experiences from Colombia (GESTIÓN Y TENDENCIAS, 2021)
This paper presents an interpretive-narrative analysis of the experiences reported by professors and teaching assistants on accounting courses at Universidad Nacional de Colombia, with the purpose of understanding the challenges, opportunities, and tensions arising during the first months of the COVID-19 pandemic, in a context of transition to online teaching. The results show behavior consistent with Bowlby's (1980) phases of mourning, moving toward a reorganization of their behaviors. The research is expected to contribute to identifying academic practices that make it easier to face unforeseen events demanding immediate change through individual and institutional effort.
Keywords: Accounting education, COVID-19, Academic practices, Learning.